VALIDITY AND RELIABILITY TESTS FOR ADMINISTRATION OF KIDNEY DISEASE QUALITY OF LIFE-SHORT FORM IN INDONESIAN VERSION - Andika, Rendy; Hamid, Agus Rizal Ardy Hariandy; Rodjani, Arry (Indonesian Journal of Urology, 2022)
Objective: This study aims to adapt the KDQOL-SF questionnaire into Indonesian and to evaluate the reliability and validity of the questionnaire in healthy subjects in Indonesia. Material & Methods: Previously translated (into Indonesian) KDQOL-SF questionnaire was given to 33 healthy subjects at Cipto Mangunkusumo General Hospital. Respondents were over 18 years old and were able to speak Indonesian orally and in written form. Reliability was measured using Alpha Cronbach’s intraclass correlation coefficient and internal consistency reliability. Validity was evaluated using Pearson’s correlation test. Results: Out of 33 respondents, the majority of subjects were male (81%) with mean age 47.4 ± 13.7 years old. The highest score was in social support aspects with mean score 99.48 ± 2.95, while the lowest score was vitality aspect with mean score 63.28 ± 11.61. Alpha Cronbach’s score was between 0.580-0.999 and Pearson’s correlation coefficient between 0.405-0.976 with P < 0.05. Conclusion: KDQOL-SF questionnaire, which was translated into Indonesian, was valid and reliable to be used in evaluating patients’ quality of before kidney transplantation in Indonesia